2011
DOI: 10.1002/app.35293
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of poly(vinyl chloride) and copolyesters based on ε‐caprolactone and L‐lactide: Miscibility, thermal stability, and weathering resistance

Abstract: Properties of the blends of Poly(vinyl chloride) (PVC) and poly(e-caprolactone) (PCLO) and copolyesters based on e-caprolactone and L-lactide (LLA) prepared by rolling were studied. Incorporating the LLA units into the structure of PCLO the content of the crystalline phase was controlled. Miscibility of the blends was assessed using DMA, and basic mechanical properties were correlated with the type and content of the polymer plasticizer. The PVC blends containing up to 20 wt parts polyesters were miscible. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…5 and 6) was comparable with the mixture containing the tin (IV)‐based stabilizer and PCL. In addition to the above‐mentioned reasons is important to mention that CL itself accelerates the dehydrochlorination of unstabilized powder PVC, increasing the rate of HCl eliminate from PVC from 16.4 to 23.3 μmol/0.2 g PVC . When CL content in PVC/CL mixture was increased to 40/100 g at the same stabilizer/initiator concentration, TS of the mixture was shortened by about one tenth (Table ), which also documents the negative effect of CL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 6) was comparable with the mixture containing the tin (IV)‐based stabilizer and PCL. In addition to the above‐mentioned reasons is important to mention that CL itself accelerates the dehydrochlorination of unstabilized powder PVC, increasing the rate of HCl eliminate from PVC from 16.4 to 23.3 μmol/0.2 g PVC . When CL content in PVC/CL mixture was increased to 40/100 g at the same stabilizer/initiator concentration, TS of the mixture was shortened by about one tenth (Table ), which also documents the negative effect of CL.…”
Section: Resultsmentioning
confidence: 99%
“…A similar decrease of TS was observed in the PVC/PCL mixtures stabilized by the same quantity of tetravalent tin‐based stabilizer in which PCL was prepared by CL polymerization initiated by another initiator type, for example, ethylmagnesium bromide . We assume that the weaker stabilization effect of dibutyltin maleate is not related to its role as the CL polymerization initiator but is caused by competitive interactions of the polyester in the areas where PVC is stabilized by the tin‐based stabilizer . Moreover, also mechanic stress during the processing of PVC/PCL mixtures undoubtedly caused stabilizer consumption, thus reducing the dehydrochlorination induction period.…”
Section: Resultsmentioning
confidence: 99%
“…Polyester plasticizers have attracted considerable attention originating from the expectation that their high molecular weight will impart unique physical and chemical properties, especially polyester plasticizers derived from fatty acid/anhydrides [12][13][14][15][16][17]. Because of their good compatibility with the polymers and excellent processibility, polyester plasticizers based on fatty acid/anhydrides are being applied as additives of functional materials with low toxicity, superior tensile properties, prominent migration resistance performance, and admirable plasticizing properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PVC has a high efficiency in forming miscible systems with several other low and high molecular weight substances acting as plasticizers. Many studies on PVC blends have reported that the intermolecular interactions of hydrogen bonding type that occur between the blend components are mainly responsible for miscibility enhancement of PVC blends . A particular interest was focused on the poly(ϵ‐caprolactone)/poly (vinyl chloride) bioblend systems which were well‐known for their molecular level miscibility through inter‐polymer hydrogen bond interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on PVC blends [11][12][13][14][15][16] have reported that the intermolecular interactions of hydrogen bonding type that occur between the blend components are mainly responsible for miscibility enhancement of PVC blends. [17,18] A particular interest was focused on the poly(e-caprolactone)/poly (vinyl chloride) bioblend systems which were well-known for their molecular level miscibility through inter-polymer hydrogen bond interactions. [19][20][21] Since then, the PCL/PVC blends are under development to search new potential applications.…”
Section: Introductionmentioning
confidence: 99%